A neural network approach to genome sequence alignment - Świniarski, Roman W.; Waagen, Donald E. (Zielona Góra: Uniwersytet Zielonogórski)
A technique for the alignment of genome sequences based on an adaptive nonlinear dynamic neural network is proposed. We present an extension to the fixed weight Hopfield neural network, creating a non-linear dynamic neural network, with weights values adaptively changing during neural processing.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka